MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) - Purwati, Purwati; Fatubun, Rainita (Journal of Honai Math, 2018)
This study aims to improve student learning outcomes on the subject of equations and quadratic inequalities using cooperative model of NHT type. This research is a Classroom Action Research, using Kemmis and Taggart model, which is implemented in three cycles. Data were observed each cycle through learning result test, student and teacher observation, and interview. The data obtained are then analyzed through: data reduction, data presentation and conclusion. The results showed that the application of NHT, the type of cooperative model can improve students' mathematics learning outcomes, especially on the subject of equations and quadratic inequalities. DOI: https://doi.org/10.30862/jhm.v1i1.733